A research report on a novel typological study of the Chinese metaphorical and metonymic idioms - Xi, Yangyang (Frontiers in Psychology, 2024)
This report shows a novel classification of the Chinese metaphorical and metonymic idioms based on the Spreading-Activation Model (SA Model). Identified first are three features of the source domain within the Chinese metaphorical and metonymic idioms: (1) the relationship between the source and target domains, (2) the number of source domains within idioms, and (3) the inherent characteristics of the source domain. Then drawing on the SA Model, this report arrives at a novel classification of the Chinese metaphorical and metonymic idioms into four categories: (1) Directional activation Idioms, (2) Cooperative activation Idioms, (3) Spreading activation Idioms, and (4) Superimposed activation Idioms. Discussion is made on each category and a continuum of cognitive difficulty is established with respect to understanding different categories. This classification is of great help within the realm of teaching Chinese as a foreign language.